Incidence and outcome of transurethral resection of prostate syndrome at a tertiary care hospital - Regmi, Prabodh; Basnet, Robin Bahadur; Subedi, Dharma Datta; Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Monopolar transurethral resection of prostate (M-TURP) is rarely complicated with the dreaded syndrome the TURP syndrome due to absorption of larger amount of non-electrolyte hypo-osmolar irrigation fluid (1.5% glycine), longer duration of surgery and larger amount of tissue resection. This study aims to find out the incidence and perioperative outcome of TURP syndrome after monopolar TURP.Method: This was a cross sectional study of retrospectively collected data during the period of 4 years from June 1st 2018 to 30th May 2022, in Department of Urology of Bir Hospital, National Academy of Medical Sciences (NAMS), Nepal. Ethical approval was obtained from NAMS ethical committee. Microsoft Excel was used for descriptive analysis of the incidence of TURP syndrome, its relation with amount of resected tissue, duration of resection time, and the outcome (need of blood transfusion, length of hospital stay, mortality).Result: Out of 208 cases of monopolar TURP, 8/208(3.8%) had TURP syndrome. Patients with TURP syndrome were age group 70-85 y. Duration of surgery was >60 min was in 5/8(62.5%), resection weight >20 gm 6/8(75%), blood transfusion 1/8(12.5%), and hospital stay >3 days in all 8/8(100%) cases. Mortality was nil in patients with TURP syndrome.Conclusion: The TURP syndrome was observed in 8/208(3.8%) and it was more common in older (>60y) with longer duration (>60 min) of surgery, and larger amount of prostatic tissue (>20gm) resection.